2015
DOI: 10.1371/journal.pone.0139238
|View full text |Cite
|
Sign up to set email alerts
|

The Small Molecule DAM Inhibitor, Pyrimidinedione, Disrupts Streptococcus pneumoniae Biofilm Growth In Vitro

Abstract: Streptococcus pneumoniae persist in the human nasopharynx within organized biofilms. However, expansion to other tissues may cause severe infections such as pneumonia, otitis media, bacteremia, and meningitis, especially in children and the elderly. Bacteria within biofilms possess increased tolerance to antibiotics and are able to resist host defense systems. Bacteria within biofilms exhibit different physiology, metabolism, and gene expression profiles than planktonic cells. These differences underscore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Biofilm can resist antibiotic killing without any drug resistance mechanisms. The link between the presence of persisters and biofilm formation is the subject of many studies [31, 32, 58, 59]. We propose that the roles of the srRNAs in persistence are associated with their biofilm formation capability, based on our findings.…”
Section: Discussionsupporting
confidence: 64%
“…Biofilm can resist antibiotic killing without any drug resistance mechanisms. The link between the presence of persisters and biofilm formation is the subject of many studies [31, 32, 58, 59]. We propose that the roles of the srRNAs in persistence are associated with their biofilm formation capability, based on our findings.…”
Section: Discussionsupporting
confidence: 64%
“…GC-MS analysis showed that the major components of T. daenensis were phenolic compounds, such as carvacrol and terpinene compounds, such as γ-terpinene and α-terpinene. Previous studies reported that EOs containing phenolic and terpinene compounds have a strong antimicrobial activity [29]. EOs of S. hortensis and O. vulgare had good antibacterial activities against S. pneumoniae.…”
Section: Discussionmentioning
confidence: 96%
“…The effect eugenol may be related to the ability to prevent biofilm organization and to disaggregate micro colonies, as demonstrated by Yadav et al (2015) against Streptococcus pneumoniae.…”
Section: Discussionmentioning
confidence: 99%